Hyperbilirubinemia and Neurodevelopmental Outcome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The results of the Collaborative Project on Preterm and Small for Gestational Age Infants in the Netherlands, 1983, in regard to hyperbilirubinemia and neurodevelopmental outcome at two years of age are reported from the Division of Neonatology, Department of Pediatrics, University Hospital, Leiden, the Netherlands.